THE EFFECT OF THE PRESENCE AND REMOVED TOTAL CARBONATE ON THE SIZE DISTRIBUTION OF SOIL SAPERATES - Salah Aldeen A. Qussab (Mesopotamia Journal of Agriculture)
Ten soil samples have been collected from different locations in Nineva province with different textures ranged from sand to clay having different content of total carbonates range from (53-265)g / kg . Each soil sample was divided in to two parts, the first one was kept on its natural condition while the total carbonate was removed from the second one . the soil particle size distribution has been measured in the presence and after removal of the total carbonate in all soil samples. The results have shown that most of the soil samples were changed to finer texture after the carbonate has been removed where as clay percents were increased and the sand percents were decrease .